(untitled) (International Journal of Engineering and Computer Science, 2014)
Course disk in either CD or DVD format can be use as teaching aids. The potential of DVD technologies has been disregarded by most of the higher education sector, especially in Nigeria. Educational research on new information and communication technologies centers more on analyzing the educational potential of products that dominate the marketplace than on developing tools particularly for teaching and learning. In Nigeria today one of the cardinal, yet ambiguous tasks in education is the evolution and employment of teaching and learning aids that effectively channel information in a format that is conducive to students as their preferred learning styles. Due to the fact that students prefer the conventional method of teaching in order to provide better understanding of conceptual theory and computational works that seem tedious manually, this platform has been developed to provide various animations, images, e-books and online resources on kinematics of machines, using the most advanced multimedia tools. All the teaching and learning materials acquired for kinematics of machines has been put in digital format and a DVD-R has been produced which contains all of the kinematics of machines software and text materials. All the video material has been digitized and various compression options are being investigated. The interactive platform is easy to integrate and access has been provided for students through a common icon based interface. This platform will help overcome the concerns of many academics about the Internet and the difficulty of integrating high quality media with a web site.